La Trypanosomiasis Americana - Mal de Chagas - Jorge Rey; Kevin Kobylinski; Roxanne Rutledge Connelly (EDIS)
ENY-726S, a 4-page illustrated fact sheet by Jorge Rey, Kevin Kobylinski and Roxanne Rutledge Connelly, is the Spanish language version of 'Blood Feeding Insect Series: American Trypanosomiasis - Chagas Disease.' It describes this potentially fatal, chronic disease and the triatomine bugs that transmit it. It discusses the low risk of contracting the disease in Florida or from contaminated blood, and information on control measures. Includes references. Published by the UF Department of Entomology and Nematology, September 2006.